Effect of a home –made milk replacer on post-weaning performance of Nubian male kids - Abdalla, Isam; Mohamed, Anfal; ElObied, Gareeballa (Gezira Journal of Agricultural Science, 2018)
The use of milk replacers to substitute valuable whole milk for feeding goat kids is not widely practiced in the Sudan. The aim of this study was to investigate the effect of a home -made milk replacer on post- weaning performance (concentrate intake, rumen development and function, live weight gain and carcass characteristics) of Nubian male kids. Ten Nubian male kids of 7 weeks age and 5.65-6.1kgs mean live weight after weaning were used. The kids were selected randomly from two groups. Group A reared on milk replacer (50% home-made milk replacer and 50% goat milk) and group B reared on goat milk and each containing 5 kids. The concentrate intake was measured daily for five weeks and body weight and mortality rate were recorded weekly. In week 3, 4 and 5 blood samples were collected for plasma urea and glucose concentration determination and were analyzed using enzymatic colorimetric methods. After 5 weeks, kids were slaughtered and body components were separated and weighed. Also, empty rumen was weighed and rumen percent from whole body live weight was calculated. The left carcass side was divided into wholesale cuts and weighed. Data were statistically analyzed for the previously mentioned parameters using SPSS program. Results showed that concentrate intake, live weight gain, slaughter weight, rumen weight and wholesale cuts except loin and best-end of neck were not significantly different. The dressing out percentage was significantly (P<0.05) higher in group B than A . Plasma urea was significantly (P<0.05) higher in treatment B than A, while glucose concentration was higher in treatment B than A, but not significant. The study concluded that goat milk could be replaced by 50% home-made milk replacer without any deleterious effects on performance of Nubian kids     استخدام بدائل اللبن كبديل للبن الطبيعي في تغذية جديان الماعز لا يمارس على نطاق واسع في السودان. الهدف من هذه الدراسة هو معرفة أثر بديل اللبن المصنع منزلياً على أداء جديان  الماعز بعد الفطام (المتناول من المركز، وتطور الكرش ووظيفتها وزيادة الوزن الحي وخصائص الذبيحة) .استخدمت 10 من جديان الماعز النوبي (ذكور) في عمر سبعة أسابيع كمتوسط  ووزن 5.65 و 6.1 كجم. غذيت الجديان على بدائل لبن مصنع منزلياً       ( 50% بديل لبن و50%  لبن ماعز). وهي المجموعة (أ)  والمجموعة )ب( غذيت على لبن الماعز كل مجموعة تحتوي على خمسة جديان بعد الفطام. قيس استهلاك العلف المركز يومياً لمدة خمسة أسابيع والوزن الحي ومعدل النقوق أسبوعياً. في الاسبوع  3و 4 و5 تم أخذ عينات دم لتحديد نسبه اليوريا و الجلكوز باستخدام طريقة قياس الطيف المرئي .ذبحت الجديان بعد الخمسة اسابيع بعد الفطام وفصلت مكونات الكرش ووزنت الكرش الفارغة وحسبت نسبة الكرش على أساس الوزن الحي. تم تقسيم الجانب الأيسر لقطعيات ووزنت. تم تحليل البيانات إحصائياً للمعاملات المذكورة سابقاً باستخدام برنامج SPSS. أوضحت النتائج انه لا توجد فروقات منويه بين المعاملات في كل من المستهلك من المركز والوزن المكتسب وزن الذبيحة والقطعيات  ووزن الكرش. بينما كانت هنالك فروقات معنوية (P≤0.05 ) في نسبه التصافي كانت أعلى في المجموعة ب. هنالك أيضاً فروقات معنوية (P≤0.05 ) في نسبه اليوريا في الدم  حيث كانت أعلى في المعاملة ب . على  الرغم من عدم وجود فروقات معنوية في تركيز الجلكوز في الدم بين المعاملات  أ و ب الا إنه  كان أعلى نسبياً في المعاملة ب. خلاصه الدراسة  يمكن استخدام بديل اللبن 50% دون اي تأثير ضار على أداء جديان الماعز النوبي.